TRENDS OF GERMINATION IN CHILLI SEEDS - ASHRAF , A; SHAHID , S; BIBI , B; MUMTAZ , M; MARRI , JK; ULLAH , I; HUSSAIN , T; KHADIM , K; ARIF , A; FAIZ , A (Biological and Clinical Sciences Research Journal, 2024)
The germination of chilli seeds has traditionally been impacted by physiological or endogenous dormancy traits. Low seed germination rates and vigor growth are issues that could contribute to the poor seedling development of the chilli crop. The most common treatment solution, gibberellic acid (GA3), is not a novel technique for breaking the dormancy of chili seeds. However, further research is required to determine the possible impact of this treatment on the germination of chilli seeds and the growth of seedlings, including the pursuit of an improved GA3 concentration. Thus, the purpose of this study was to assess how various GA3 concentrations affected the performance of seedling growth and emergence in chilli. FGP and GRI had maximum value for T2, and all the treatments were highly significant for FGP and significant for GRI. In T3, the germination performance of the seed decreased drastically. MGT (MGT) decreased from control to T2 and then increased in T3. All three treatments were significantly different for MGT. SH and SVI had maximum values for T2, and all three treatments were significantly different from each other for SVI and highly significant for SH. The optimum concentration of GA3 as pretreatment of chilli seed will help better germination and healthy crop in turn.